Investigation of heat stress and heat strain in outdoor workers: a case study in Iran - Golbabaei, Farideh; Monazzam, Mohammad Reza; Yazdani Aval, Mohsen; Allahyari, Teimour; Taban, Ebrahim; Rostami Aghdam Shendi, Maryam (Archives of Advances in Biosciences, 2016)
Heat stress is an important and serious threat at work and is a particular concern in outdoor occupational environments. This study aims at comparing heat stress and heat strain at different outdoor groups, examining the protective and adaptive actions which were done by workers and also provi services to them by government or employer to reduce heat load. This cross–sectional study was conducted in the hottest days of the summer 2015 in Shabestar, Iran and 53 healthy men in nine occupational groups including concrete makers, porters, construction, waste site and road making workers, stonemasons, farmers, traffic officers, and street vendors participated. A set of physiological parameters, like heart rate, blood pressure, skin temperature and etc., WBGT index details and some of the adaptive and protective parameters were measured and monitored simultaneously at different times of the day. The study finds that heat exposure in outdoor workplace is prevalent and WBGT TWA/TLVave is less than 1 in some groups like stonemasons, waste site workers, traffic officers and street vendors whereas in other studied occupations, it is more than 1.This matter is compounded by the fact that the provision of health services by employers or local government was limited, and almost all of the participants had poor or insufficient access levels to public health and welfare services. This study confirms the necessity of interventions by a range of factors, such as government plans, improvement of services in the prevention of heat stress, and planning training courses for outdoor workers to build their knowledge of heat stress.